GAMIFIED HYBRID LEARNING FOR NEURODIVERSE STUDENTS: DESIGNING UNIVERSALLY ACCESSIBLE INSTRUCTIONAL MODELS - Rachid Belhaj; Nadia Ait Ali; Ibrahim Browlahrouf (Yayasan Adra Karima Hubbi, 2025)
The increasing presence of neurodiverse learners in mainstream educational environments has necessitated a rethinking of instructional models to ensure equitable access and participation. Traditional pedagogical approaches often fail to accommodate the diverse cognitive profiles and sensory needs of students with conditions such as autism spectrum disorder (ASD), ADHD, and dyslexia. This study explores the design and implementation of gamified hybrid learning environments aimed at enhancing engagement, inclusivity, and learning outcomes for neurodiverse students. The primary objective is to develop universally accessible instructional models that integrate gamification principles with hybrid learning modalities. Using a design-based research methodology, the study was conducted across three inclusive secondary schools with 72 neurodiverse students over two academic terms. Data were collected through classroom observations, semi-structured interviews, and learning analytics. Results indicate that gamified hybrid learning models significantly improved students’ focus, motivation, and task completion rates, particularly when game elements were personalized to align with students' sensory preferences and learning styles. Teachers reported increased flexibility in instructional delivery and greater student participation. The study concludes that gamified hybrid instruction represents a promising pathway toward universal design for learning (UDL), supporting both academic achievement and psychological safety for neurodiverse learners.